Doing and being occupation centred in challenging settings: reflections on implementation strategies and professional rewards/ Ser e fazer centrado na ocupação em ambientes desafiadores: reflexões sobre estratégias de implementação e recompensas profissionais - Whiteford, Gail Elizabeth; Jones, Katherine; Weekes, Gemma; Ndlovu, Nomagugu; Long, Cassandra (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: In order to centralise occupation in challenging settings, therapists need a supportive process and distinct strategies to assist them as they re-design and implement services which are truly occupation centred, based and focussed. Objectives: The aim of this article is to illuminate the strategies utilised by a group of occupational therapists working to centralise occupation in a forensic mental health service in Australia. It also highlights the subsequent professional rewards they experienced from being more occupation centred in everyday practice. Method:A Community of Practice Scholars was formed by participants. They then used a Practice Based Enquiry (PBE) approach – a type of action methods research - involving iterative cycles of data collection, analysis, critique and implementation of practice innovations. Results: Seven major themes emerged from the study. The theme of Strategies in, and Rewards of, Occupation Centred Practice is the focus of this article, with inclusion of data from the theme of Communicating with Certainty. Additional themes are discussed through other, related publications. Conclusion: This article highlights the process of moving beyond “knowing that” occupation centred practice is important, to “knowing how” to re-design an occupational therapy service to achieve this aim. Becoming more occupation centred in practice can be experienced as more professionally rewarding for occupational therapists, especially those working in challenging settings.